PERSEPSI MAHASISWA PENDIDIKAN GEOGRAFI TENTANG PELAKSANAAN PRAKTEK LAPANGAN KEPENDIDIKAN - Budi Yusri; Ernawati Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This research aims to describe the perception of geography education students about implementation of educational field practice (PLK), which is divided into three stages, i.e. 1) pre-activity, 2) implementation of activities, and 3) post-activity. This type of research is quantitative with descriptive method which using questionnaire as the research instrument. The population of this research is 113 students of geography education 2015 who had implemented PLK. The research sample was 86 students based on the Kracjie table and selected by the simple random sampling method. The results of this study indicate that the perceptions of geography education students about the implementation of PLK are in the sufficient category in the value range 78-121, with details in the pre-activity stage is in the deficient category, the implementation stage is in the sufficient category, and the post-activity stage in the good category.